Relationship between oxygen uptake levels and capacity of intestinal sacs for sugar active transport (Revista Española de Fisiología, 1969)
This work includes the study of the influence that the metabolic level of indi vidual intestinal sacs of rats, measured by the oxygen uptake, have on the active transport of galactose and 3-O-methyl- glucose. The experiments showed a statis tically significative correlation between both processes.